LOTIN TILIDA TIBBIY TERMINOLOGIYANI O‘QITISHDAGI MUAMMOLAR VA ULARNI HAL ETISH YO‘LLARI (TAMADDUN NURI JURNALI, 2024)
This article discusses common challenges faced by medical students in learning Latin terms and explores effective methods to address these obstacles, including contextual learning, mnemonics, and interactive methods.